2005
DOI: 10.3354/meps288183
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of euphausiids off northern California and effects of short time-scale wind events on Euphausia pacifica

Abstract: Variability in upwelling conditions has been shown to change the physical and biological characteristics of the water over the California shelf, including the population biology of the dominant euphausiid Euphausia pacifica. However, on a short time-scale (ca. weekly), far less is known, especially for larger planktonic animals like euphausiids. We examined E. pacifica abundance, size structure, oocyte composition, and euphausiid egg abundance in an upwelling region off northern California

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Further, the degree to which primary production and zooplankton grazing are coupled is still not clear and neither is the role of mesozooplankton, which appear to make direct use of a substantial portion of the primary production, as much as 15-50% in non-tropical shelf areas (Walsh, 1983;Baars and Fransz, 1984;Landry and Lorenzen, 1989;Bathmann et al, 1990). Subject to water-borne transport, zooplankton exhibit changes in distribution over diurnal and synoptic time scales (e.g., Smith et al 1981;Dorman et al 2005), but questions remain about the net advection of zooplankton over time scales of life expectancy and how effective zooplankton populations are in holding their position over the shelf (e.g., through ontogenetic migration, Peterson et al 1979, or diel vertical migration, Wroblewski 1982 or becoming concentrated in bays (e.g., Graham et al 1992;Wing et al 1998;Roughan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the degree to which primary production and zooplankton grazing are coupled is still not clear and neither is the role of mesozooplankton, which appear to make direct use of a substantial portion of the primary production, as much as 15-50% in non-tropical shelf areas (Walsh, 1983;Baars and Fransz, 1984;Landry and Lorenzen, 1989;Bathmann et al, 1990). Subject to water-borne transport, zooplankton exhibit changes in distribution over diurnal and synoptic time scales (e.g., Smith et al 1981;Dorman et al 2005), but questions remain about the net advection of zooplankton over time scales of life expectancy and how effective zooplankton populations are in holding their position over the shelf (e.g., through ontogenetic migration, Peterson et al 1979, or diel vertical migration, Wroblewski 1982 or becoming concentrated in bays (e.g., Graham et al 1992;Wing et al 1998;Roughan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged upwelling-favourable winds decreased the reproductive effort and abundance of E. pacifica both on short-and inter-annual time scales (Dorman et al, 2005). Accordingly, there may be an optimal upwelling intensity which supports reproduction in euphausiids by favouring primary and secondary production without advecting plankton too far off-shore (Dorman et al, 2005), especially in species such as E. hanseni, which releases eggs in the surface layers which are then transported offshore (Barange and Pillar, 1992). However, further analyses are needed to detail the ovarian development cycle in E. hanseni females as it relates to upwelling and food availability and to clarify whether this species spawns continuously or in multiple discrete periods (Siegel, 2000).…”
Section: Influence Of Ms and Sds On Oxygen Uptakementioning
confidence: 95%
“…In the southern Benguela Current, Euphausia lucens spawned before the onset of upwelling and the spring phytoplankton bloom associated with it (Pillar and Stuart, 1988), thereby ensuring that the larvae hatched during a period of high food supply. Dorman et al (2005) showed that short time-scale fluctuations in Chl a concentrations due to changes in the upwelling state positively affect the amount of eggs spawned by Euphausia pacifica. Spawning intensities for E. pacifica were highest during upwelling events due to high food supply (Brinton, 1976;Smiles and Pearcy, 1971).…”
Section: Influence Of Ms and Sds On Oxygen Uptakementioning
confidence: 99%
See 2 more Smart Citations